The non‐visual opsins: eighteen in the ancestor of vertebrates, astonishing increase in ray‐finned fish, and loss in amniotes. Issue 7 (23rd October 2017) - Beaudry, Felix Emile Gastonguay; Iwanicki, Tom W.; Mariluz, Bertha Ruth Zelada; Darnet, Sylvain; Brinkmann, Henner; Schneider, Patricia; Taylor, John Stewart
Abstract: Non‐visual opsins were discovered in the early 1990s. These genes play roles in circadian rhythm in mammals, seasonal reproduction in birds, light avoidance in amphibian larvae, and neural development in fish. However, the interpretation of such studies and the success of future work are compromised by the fact that non‐visual opsin repertoires have not been properly characterized in any of these lineages. Here, we show that non‐visual opsins from tetrapods and ray‐finned fish are distributed among 18 monophyletic subfamilies. An amphibian sequence occurs in every subfamily, whereas mammalian orthologs occur in only seven. Species in the major ray‐finned fish lineages, Holostei, Osteoglossomorpha, Otomorpha, Protacanthopterygii, and Neoteleostei, have large numbers of non‐visual opsins (22–32 genes) as a result of gene duplication events including, but not limited to, the teleost genome duplication (TGD). In contrast to visual opsins, where lineage‐specific duplication is common, the ray‐finned fish non‐visual opsin repertoire appears to have stabilized shortly after the TGD event and consequently even distantly related species have repertoires of similar size and composition. Most non‐visual opsins have been named without the benefit of a phylogenetic perspective and, accordingly, major revisions are proposed. GRAPHICAL ABSTRACT: Non‐visual opsins from tetrapods and ray‐finned fish are distributed among 18 monophyletic subfamilies. An amphibian sequence occurs in every sub‐family, whereas mammalian orthologs occur in only seven. Species in the major ray‐finned fish lineages, Holostei, Osteoglossomorpha, Otomorpha, Protacanthopterygii, and Neoteleostei, have large numbers of non‐visual opsins (22–32 genes) as a result of gene duplication events including, but not limited to, the teleost genome duplication (TGD). In contrast to visual opsins, where lineage‐specific duplication is common, the ray‐finned fish non‐visual opsin repertoire appears to have stabilized shortly after the TGD event and consequently even distantly related species have repertoires of similar size and composition.